El nuevo proceso de ejecución de reparación económica en el seno de la jurisdicción contencioso administrativa - Velasteguí Ayala , Ximena (2017)
This essay studies the process of implementation of existing economic repair in charge of the judges of the district courts of Contentious Administrative Law in the country, as ordered by the Constitutional Court in judgement N.º 011-16-SIS-CC, issued in case N.º 0024-10-IS, which unifies the procedure to be followed for the purpose of quantifying the amount of economic repair. This rule is specified in a judicial guarantees statement, providing always that the obligor to pay is the State under the frame of the provisions of article 19 of the Law for Organic Jurisdictional Guarantees and Constitutional Control. This fault arises as a response to the problem of non-constitutional rulings.